1998
DOI: 10.1093/carcin/19.12.2201
|View full text |Cite
|
Sign up to set email alerts
|

(-)-Epigallocatechin-3-gallate inhibition of ultraviolet B-induced AP-1 activity

Abstract: Green tea polyphenols have been shown to inhibit cancer in a variety of tumor models, including ultraviolet B (UVB)-induced non-melanoma skin cancer. In green tea extracts, the major dry mass constituent is the family of catechins, of which (-)-epigallocatechin-(3)-gallate (EGCG) is considered to be important for the chemopreventive activity. EGCG has been shown to have antioxidant properties, but there has been little progress toward identifying the specific targets and mechanisms of its action. Using culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(73 citation statements)
references
References 24 publications
0
72
0
1
Order By: Relevance
“…Previously, we have shown that EGCG, a polyphenol compound isolated from green tea, not only decreased UVB induced AP-1 activation and c-fos expression, but also inhibited UVB induced p38 activation in human keratinocytes (Barthelman et al, 1998b;Chen et al, 1999b). These results implied that the mechanism of EGCG inhibition of UVB induced AP-1 activation and c-fos expression might be through inhibition of p38 activation.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Previously, we have shown that EGCG, a polyphenol compound isolated from green tea, not only decreased UVB induced AP-1 activation and c-fos expression, but also inhibited UVB induced p38 activation in human keratinocytes (Barthelman et al, 1998b;Chen et al, 1999b). These results implied that the mechanism of EGCG inhibition of UVB induced AP-1 activation and c-fos expression might be through inhibition of p38 activation.…”
Section: Discussionmentioning
confidence: 69%
“…These results indicated that c-fos expression might play a key role in UVB induced AP-1 activation in human keratinocytes. (7)-Epigallocatechin gallate (EGCG), a chemoprevention agent isolated from green tea, inhibited UVB induced c-fos gene expression and AP-1 activation (Chen et al, 1999b;Barthelman et al, 1998b). It appears that c-fos could be a target gene for chemoprevention of skin cancer.…”
Section: Introductionmentioning
confidence: 99%
“…(n ϭ 3). scription factors, including NFB (43,44), c-fos (45,46), junB, junD and Fra-1 (8), and signal transducers and activators of transcription (STAT) (47), the present study is the first to define C/EBP as a target. The findings from our present study, when considered with our previous study (8), suggests that EGCG triggers a Ras, MEKK1, MEK3, p38␦ cascade that, in turn, increases C/EBP factor level and increases complex formation on the hINV promoter C/EBP site.…”
Section: Fig 6 Curcumin Inhibits Carasand Mekk1-dependent Hinv Prommentioning
confidence: 85%
“…Third, chemopreventive agents can produce different responses in normal versus immortalized/transformed keratinocytes. Thus, in normal keratinocytes EGCG increases AP1 factor levels, while in immortalized/transformed keratinocytes EGCG treatment reduces AP1 factor expression (Nomura et al, 2000;Dong et al, 1997;Barthelman et al, 1998;Chung et al, 1999). This suggests that the activity and mechanism of chemopreventive agent action may change during disease progression.…”
Section: Discussionmentioning
confidence: 99%